La concepción de “ser humano” en Pablo Freire - Pineda Ibarra, Roberto (Revista Electrónica Educare, 2008)
This article analizes how Pablo Freire, one of the main education theoreticians with broad trajectory and world influence and with a big contibution to what it is known as alternative pedagogy, conceives the human been and his participation in and with the world. He has built his conception on this matter through several publications, merged from his teaching practice.